Category of agent conceptualization in the light of distributed model of language and culture - Kolmogorova, A. V. (Cognition, Communication, Discourse, 2018)
The article discusses the results of experimental research of social cognition as the basis for individuals’ environment conceptualization. The attention is focused on the particular features of agent conceptualization in Russian linguistic consciousness.